Distributional impacts of agricultural policies in Zambia: A microsimulation approach - Katrin Gasior; Silvia Navarro; Jukka Pirttilä; Mari Kangasniemi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines the distributional impacts of agricultural policies versus those of cash transfers using a tax-benefit microsimulation model for Zambia for the policy year 2020. The analysis also considers the behavioural impacts of input subsidies and social cash transfers. The results indicate that Zambian agricultural policies reduce headcount poverty by 3-5 percentage points, depending on whether only their direct impacts or also behavioural impacts that lead to changes in agricultural production are taken into account. The paper also considers policy reforms where the goal is to achieve similar, or even greater, poverty reduction with smaller government net expenditure. The results from these simulations suggest that it is feasible to achieve this goal by better targeting input subsidies to more needy households, increasing the benefit amounts that reach the poorest part of the population, and by using direct benefits instead of indirect tax expenditures. The results, however, also highlight that the final impacts on poverty and inequality are heterogeneous across population groups.
Keywords: H23; H24; O12; Q18; 330; agricultural policies; tax; cash transfers; poverty; inequality; Zambia